THE (IR)RELEVANCE OF BIBLICAL SCHOLARSHIP?: A CHALLENGE, AND AN OPPORTUNITY - Giffone, Benjamin D. (Scriptura, 2021)
Has biblical scholarship become irrelevant to modern secular societies? Are the threats to the viability of biblical scholarship of the same nature as the threats to other areas of the humanities (history, philosophy, literature), or is there a qualitative difference? What about the role of technology in biblical research and biblical education? What is the future of the institutions of biblical scholarship such as universities, seminaries, journals, and academic presses? What is the role of biblical scholars in secular and post-secular societies, as contrasted with scholars in/from emerging communities? This essay argues that the problem of "validation" lies at the heart of biblical scholarship’s irrelevancy within the broader secularity of modern world and that this problem is even more evident in the scholarly discourse coming from regions like Eastern Europe and South Africa. However, the loss of authority of biblical scholarship more generally represents an opportunity for these communities. Rather than becoming enamoured of validation from the North Atlantic world, Bible-reading communities must cultivate their own forms of validation based in their unique histories with the Bible, and the affinities between their own histories/cultures and the cultures that produced the Old and New Testament texts.